Optimizing Generation Z Employee Performance Through Soft Skills, Hard Skills, And Work–Life Balance: The Mediating Role Of Job Satisfaction At PT Bank Riau Kepri Syariah, Riau Province - Sri Indrastuti; Gilang Nugroho; Amries Rusli Tanjung; Fuji Dwi Citra Resmi (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
This study aims to analyze the effects of soft skills, hard skills, and work–life balance on the performance of Generation Z employees, with job satisfaction serving as an intervening variable, at PT Bank Riau Kepri Syariah, Riau Province. This research employed a quantitative approach, with data collected through a questionnaire. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that hard skills and work–life balance have a positive and significant effect on job satisfaction, whereas soft skills do not have a significant effect. Furthermore, soft skills and job satisfaction have a positive and significant effect on employee performance, while hard skills and work–life balance do not have a direct significant effect on employee performance. The mediation analysis reveals that job satisfaction mediates the effects of hard skills and work–life balance on employee performance but does not mediate the effect of soft skills. These findings suggest that improving hard skills and implementing an effective work–life balance should be supported by enhanced job satisfaction to improve the performance of Generation Z employees. Therefore, organizations are encouraged to strengthen employees' soft skills through training programs, teamwork development, and emotional intelligence enhancement.